Lactylation and tumor immune regulation: insights from recent studies - Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Wang, Qiang (Frontiers in Immunology, 2026)
Lactate, a major product of glycolysis, accumulates abundantly in the tumor microenvironment (TME), serving not only as a hallmark of metabolic dysregulation but also as a key driver of immunosuppression. In recent years, lysine lactylation (Kla), a novel post-translational modification (PTM), has been identified, linking lactate metabolism closely with epigenetic regulation. Current studies indicate that lactylation modulates gene transcription and metabolic pathways in tumor cells while broadly influencing immune cell functions. For example, histone lactylation in macrophages promotes M2 polarization, enhancing immunosuppressive phenotypes; T cells, natural killer (NK) cells, dendritic cells (DCs), and myeloid-derived suppressor cells (MDSCs) may also be regulated by lactylation, thereby affecting anti-tumor immune responses and the efficacy of immune checkpoint inhibitors. As the mechanistic understanding of lactylation deepens, its roles in tumor immune evasion and therapy resistance are becoming increasingly evident. Targeting lactate metabolism and lactylation-related enzymatic processes, potentially in combination with immunotherapy, may represent a promising therapeutic strategy. This mini-review summarizes recent advances in lactylation research in tumor immunity and discusses its potential clinical implications and future directions.